2020
DOI: 10.1002/hyp.13857
|View full text |Cite
|
Sign up to set email alerts
|

Near‐real‐time one‐kilometre Soil Moisture Active Passive soil moisture data product

Abstract: The coarse resolution soil moisture (SM) data from NASA SMAP mission have been steadily produced with the expected performance since April 2015. These coarse resolution observations could be downscaled to fine resolution using fine scale observations of SM sensitive quantities from existing satellite sensors. For operational users who need near‐real‐time (NRT) high resolution SM data, the downscaling approach should be feasible for operational implementation, requiring limited ancillary information and primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In general, the application of aforementioned downscaling techniques enhances the spatial resolution of passive microwave SM with varying degrees of accuracy. However, most of these techniques are predominantly applied to the arid and semi-arid climatic regions, and their performances are often site-specific (e.g., [22,25,28,53]), requiring further investigation across diverse geographical and climatic regions with a range of land cover types.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the application of aforementioned downscaling techniques enhances the spatial resolution of passive microwave SM with varying degrees of accuracy. However, most of these techniques are predominantly applied to the arid and semi-arid climatic regions, and their performances are often site-specific (e.g., [22,25,28,53]), requiring further investigation across diverse geographical and climatic regions with a range of land cover types.…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture is known as a key variable for agricultural drought monitoring in a multitude of studies (Berg & Sheffield, 2018; Gavahi et al., 2020; Hao & AghaKouchak, 2013; Martínez‐Fernández et al., 2016; L. Xu et al., 2020, 2019; Y. Xu et al., 2018; Yin et al., 2020). Moreover, soil moisture is an important component in the hydrological cycle, which is estimated through in situ stations, satellite remote sensing, or hydrologic modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial resolution of the soil moisture data derived by satellite are still coarse while hydrological‐ and agricultural applications require finer‐scale (kilometer or sub‐kilometer) soil moisture data due to spatial heterogeneousness (i.e., land use, vegetation, and topography) in regional or local areas (Hssaine et al., 2021; Tian et al., 2020). Different downscaling approaches are developed based on the need of high‐resolution soil moisture data (Guevara & Vargas, 2019; Montzka et al., 2018; Yin et al., 2020). Moreover, recent studies have utilized 1 km scale soil moisture data for drought monitoring and revealed finer resolution data provide more detailed information in heterogeneous areas (Abbaszadeh et al., 2021, 2019; Fang et al., 2021; Gavahi et al., 2020; Yin et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration crucially depends on near-surface water content; hence having accurate observations and estimates of global soil moisture is vitally important [11]. Unfortunately, current remote sensing observations of soil moisture are on the kilometric spatial scale or greater [12], [13], whereas some NFM practices (such as land-and soil-based management) occur on sub-kilometric spatial scales (i.e., individual field scale) [14]. In order to better understand the variability of soil moisture across different agricultural practices (such as the comparison of different fields and farms) within the context of NFM practices, finer resolution observations of soil moisture are required.…”
Section: Introductionmentioning
confidence: 99%